ANALISIS IMPLEMENTASI PERANAN GURU DALAM ADMINISTRASI DAN MANAJEMEN PENDIDIKAN - Zebua, Feliks Rejeki Sotani (Jurnal Inovatif Manajemen Pendidikan Islam, 2023)
This study aims to analyze the implementation of the role of teachers in education administration and management using a qualitative descriptive analysis method with a library research approach. The focus of the study includes the role of teachers in time management, conflict management, communication with students, parents, and colleagues, and relationships with the community. Data were obtained through analysis of relevant literature. The results show that teachers have important roles in education administration and management, including time management, conflict resolution, effective communication and good relationships with all related parties. Effective implementation of these roles will contribute to the creation of a conducive learning environment, harmonious relationships between all parties involved and the successful operation of the education system.